The Methodology of Professional Competencies Formation for The Specialists in Environmental Monitoring on the Basis of Synergistic Pedagogics - BORDIUG, NATALIA; ALPATOVA, OKSANA; ISHCHUK, OKSANA; SVITELSKYI, MYKOLA; SMAGLY, VIKTOR (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
The issues of professional training for future environmental engineers training are considered in the article. The methodical bases of teaching environmental monitoring have been developed and substantiated for the application in the learning process through the implementation of inter-disciplinary approach. The basic components of training future environmental engineers have been defined and analysis of the formation of professional system-modeling competencies in environ-mental monitoring have been conducted.